Recommending early integration of palliative care - Does it work? - Gaertner, Jan; Wolf, Juergen; Frechen, Sebastian; Klein, Ursula; Scheicht, Dennis; Hellmich, Martin; Toepelt, Karin; Glossmann, Jan Peter; Ostgathe, Christoph; Hallek, Michael; Voltz, Raymond (Supportive Care in Cancer, 2012)
Background: In 2006, our comprehensive cancer center decided to implement early integration (EI) of palliative care (PC) by (a) literally adopting the WHO definition of PC into cancer care guidelines and (b) providing a PC consulting team (PCST) to provide EI on in- and outpatient wards. The experience with this approach was assessed to identify shortcomings. Methods: A retrospective systematic chart analysis of a 2-year period was performed. Results: A total of 862 patients were treated (May 2006-April 2008). Many patients consulted by the PCST for the first time were already in a reduced performance status (ECOG 3 & 4: 40%) or experiencing burdening symptoms (i.e., dyspnoea 27%). After the first year (period A; "getting started"), the overall prevalence of symptoms identified on first PC contact decreased from seven to three, (p∈<∈0.001) as well as surrogate measures for advanced disease (i.e., frailty: from 63% to 33%; CI: [-36%; -23%], p∈<∈0.001). Conclusion: Surrogate measures (symptom burden, performance status) indicate that PC was integrated earlier in the course of the disease after a 1-year phase of "getting started" with EI. Yet, the WHO recommendation alone was too vague to successfully trigger EI of PC. Therefore, the authors advocate the provision of disease specific guidelines to institutionalize EI of PC. Such guidelines have been developed for 19 different malignancies and are presented separately. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2025-10-27
Keywords: Cancer; Early integration; Palliative care; Patient